(untitled) (The Journal of Building and Land Development, 2025)
Land acquisition and aggregation are essential for urban development projects and sustainable land use planning. To achieve this, it is important to have appropriate funding methods for land acquisition to avoid obstacles caused by displacement. There are various financing options for compulsory land acquisition and aggregation, but the ideal one depends on the specific land gap that needs to be filled. Choosing the right financing method is crucial to ensure the project’s success and avoid negative impacts on the affected individuals and overall development goals. This research examines how different financing methods used in land acquisition and aggregation affect the success of urban development projects in Dar es Salaam city. Data from 11 land acquisition projects and 179 respondents based on a survey questionnaire were analysed to identify contributing factors to project success. The analysis was done through descriptive statistics and a binary logistic regression model. Findings suggest that equity and partner contribution financing, effectively bridge the funding gap for land acquisition and aggregation projects. Private entities often use them as they increase the likelihood of success, but such approaches need to be complemented with expropriation, whether through local or central government. By leveraging both these modalities, projects can be adequately funded and completed as planned. Keywords: Land acquisition, Financing methods, Project success, Community